Public infrastructure procurement: A review of adversarial and non-adversarial contracting methods - Regan, M.; Love, Peter; Smith, J. (PrAcademic Press, 2015)
© 2015 by PrAcademics Press. Adversarial contracting methods are used for most public infrastructure procurement and timely delivery on budget remains a problem. In the past 20 years, OECD countries have adopted a number of alternative procurement methods that are based on collaborative principles including public private partnerships, long-term outsourcing arrangements and relationship/alliance contracts. We review the theoretical principles that operate for both adversarial and collaborative contracting methods. We identify the characteristics of non-adversarial contracting methods such as the output specification, qualitative selection criteria, the alignment of incentives, discrete allocation of residual control rights, life cycle costing, and risk-weighted value for money measurement that are delivering better procurement outcomes for government.